Cohort study of patients with advanced cancer: outcomes associated with duration of antibiotic therapy for non-ventilator hospital-acquired pneumonia - Seohyuk Lee; Jemma Benson; Avi Cohen; Vincent Quagliarello; Manisha Juthani-Mehta; Rupak Datta (Cambridge University Press, 2024)
In this single-center observational study of 118 older adults with advanced cancer who developed non-ventilator hospital-acquired pneumonia, prolonged antibiotic durations (8-14 and ≥15 vs ≤7 d) were not associated with reduced adjusted odds of 90-day all-cause readmission or death. These data may inform antimicrobial stewardship efforts in palliative care settings.